2020
DOI: 10.1515/jpem-2019-0439
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of children with phenylketonuria

Abstract: BackgroundDiet plays an integral role in the maintenance of oral health, but dietary modifications due to medical problems such as phenylketonuria (PKU) can have adverse effects on oral health. This descriptive study was performed to evaluate the oral health status of children with PKU.MethodsOne hundred and ninety-seven patients with PKU aged between 1 and 22 years were evaluated. Clinical evaluations were performed by one experienced dentist regarding dental caries, gingival health and dental erosion. Catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…However, significantly greater number of children with PKU exhibited the signs of tooth wear compared to their healthy counterparts (33% vs. 24%). More recently, in line with our results, Ballikaya et al ( 13 ), reported higher caries prevalence among PKU patients. Nevertheless, it should be noted that their study primarily examined very young patients (1 to 5 years old) and only a small percentage (16.2%) of children was older than 11 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, significantly greater number of children with PKU exhibited the signs of tooth wear compared to their healthy counterparts (33% vs. 24%). More recently, in line with our results, Ballikaya et al ( 13 ), reported higher caries prevalence among PKU patients. Nevertheless, it should be noted that their study primarily examined very young patients (1 to 5 years old) and only a small percentage (16.2%) of children was older than 11 years.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Lucas et al ( 18 ), found a significantly greater mean plaque score for 41 PKU patients compared with controls. Ballikaya et al ( 13 ), found moderate plaque accumulation and gingival inflammation in PKU patients, with nearly all of them requiring professional oral hygiene procedures due to excessive plaque and calculus. The scores for several oral hygiene indices were noticeably higher for our PKU patients compared to their controls, thus indicating an increased periodontal disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…Since there has been no other report on oral health indices of patients with MSUD, we could only compare the oral health results of MSUD with the data of patients with PKU. Studies evaluating the oral health status of children with PKU are few and have conflicting results [ 10 – 12 ]. Most studies in children with PKU have revealed a similar or lower prevalence of caries compared to healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…A low rate of caries despite a highly cariogenic diet might result from high phenylalanine (the accumulating amino acid in PKU), which has been considered to possibly act as a factor that limits the growth of plaque microorganisms [ 10 , 11 ]. In a study performed at the same clinic, we have reported the prevalence of dental caries in 132 well-treated PKU patients as 67% [ 12 ]. Although dental caries in MSUD patients was higher than the PKU patients in that study; these differences might be attributed to the oral health behaviors, diet, and concomitant diseases such as epilepsy or intellectual disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation